Biomimetic Autocatalytic Synthesis of Organized Silica Hybrids. Issue 22 (17th July 2015) - Licsandru, Erol; Petit, Eddy; Moldovan, Simona; Ersen, Ovidiu; Barboiu, Mihail
Abstract: Biogenic formation of silica is a fundamental process occurring under mild conditions. Here we report autocatalytic generation of silica hybrid materials. Self‐organized siloxanes containing imidazole self‐catalytic groups can be transformed to hybrid silica by using mild biomimetic conditions similar to those under which primitive organisms make silica. Abstract : Biomimetic formation of self‐organized silica hybrids can be achieved by self‐catalytic processes. Active imidazole moieties catalyze hydrolysis/condensation reactions in the absence of conventional sol–gel catalysts. Siloxane–imidazole proxy interactions are beneficial for the synthesis. As in natural systems, highly organized hybrid silica can be obtained with a very high degree of control.